PENGARUH STRES KERJA, FAKTOR LINGKUNGAN, DAN BUDAYA ORGANISASI TERHADAP KINERJA AUDITOR INDEPENDEN (Studi Pada Auditor Independen Kantor Akuntan Publik Di Surabaya) - Novi Darmayanti (J-MACC, 2018)
This research aims to knows the relationship of work stress, environmental factors and organization custom on independent auditor performance and obtain emprical evidence on the factors related to the behavior of auditors that could affect the performance auditor work in Public Accounting Firm in Surabaya. The data are analyzed by multiple linear regression analysis method supported by SPSS program ver. 23.0, writers deployed 70 questionnaires to the auditors worked on the Firm in Surabaya where questionnaires were successfully returned as many as 58 questionnaires, While there are 12 questionnaires that did not return and reply, so that 58 samples were used in this study. The taking of sampling is by using tables Isaac & Michael. The results partially of this study showed that work stress have positive and significant effect on auditor’s performance, environmental factors have positive and significant effect on auditor’s performace, organizational culturehas a significant effect on auditor performance, so simultaneously work stress, environmental factors, and organizational culture have positif and significant effect on auditor performance.